Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/adfm.201804388
|View full text |Cite
|
Sign up to set email alerts
|

A MoSe2/WSe2 Heterojunction‐Based Photodetector at Telecommunication Wavelengths

Abstract: van der Waals (vdW) heterojunctions enable arbitrary combinations of different layered semiconductors with unique band structures, offering distinctive band engineering for photonic and optoelectronic devices with new functionalities and superior performance. Here, an interlayer photoresponse of a few-layer MoSe 2 /WSe 2 vdW heterojunction is reported. With proper electrical gating and bias, the heterojunction exhibits highsensitivity photodetection with the operation wavelength extended up to the telecommunic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 48 publications
(31 reference statements)
0
76
0
Order By: Relevance
“…This observation rules out the contribution of sub-bandgap traps (if any) in the photocurrent generation across the interlayer bandgap. 58,59 Absence of photoresponse in an individual WSe2 FET (inset in Figure 6e) when subjected to IR radiation under the same set-up reinforces the sub-bandgap (type-II) interlayer photogeneration across the heterointerface. A schematic depicting the energy range involved in the optical measurements in comparison to the DFT interlayer bandgap values and the bandgaps of individual WSe2 and ReS2 layers is shown in Figure 6f for better visualization.…”
Section: Photovoltaic Effect and Ir Photoresponsementioning
confidence: 70%
“…This observation rules out the contribution of sub-bandgap traps (if any) in the photocurrent generation across the interlayer bandgap. 58,59 Absence of photoresponse in an individual WSe2 FET (inset in Figure 6e) when subjected to IR radiation under the same set-up reinforces the sub-bandgap (type-II) interlayer photogeneration across the heterointerface. A schematic depicting the energy range involved in the optical measurements in comparison to the DFT interlayer bandgap values and the bandgaps of individual WSe2 and ReS2 layers is shown in Figure 6f for better visualization.…”
Section: Photovoltaic Effect and Ir Photoresponsementioning
confidence: 70%
“…2D materials have good application prospects in the field of photodetectors due to their excellent optical and electronic properties. At present, many photodetectors based on 2D materials have been reported and have exhibited excellent photodetection performance . Xia et al demonstrated a single‐layer and few‐layer graphene‐based transistor photodetector with ultrafast photoresponse characteristics, wide optical absorption wavelength, and good internal quantum efficiency.…”
Section: The Emergence Of 2d Materialsmentioning
confidence: 99%
“…At present, many photodetectors based on 2D materials have been reported and have exhibited excellent photodetection performance. [151][152][153][154][155][156] Xia et al [157] demonstrated a single-layer and few-layer graphene-based transistor photodetector with ultrafast photoresponse characteristics, wide optical absorption wavelength, and good internal quantum efficiency. Although graphene photodetectors exhibit excellent photodetector behavior, [158][159][160][161] it is difficult to open zero bandgaps, and low light absorption [162][163][164] (only 2.3% light absorptivity) limits its application in photodetection devices.…”
Section: Application Of 2d Materials On Photodetectorsmentioning
confidence: 99%
“…In addition to mechanically exfoliated nanosheets, materials prepared with chemical vapor deposition (CVD) can also be manually stacked . Many heterostructures have been produced, such as MoS 2 /WS 2 , graphene/MoS 2 , MoSe 2 /graphene, and MoS 2 /WSe 2 , for flexible IR photodetectors and image sensor arrays.…”
Section: Production Of 2dhsmentioning
confidence: 99%